Viability and contribution to proteolysis of an adjunct culture of Lactobacillus plantarum in two model cheese systems: Cheddar cheese-type and soft-cheese type - Milesi, Maria Mercedes (2008)
Aims: The influence of the cheese-making process, ripening conditions and primary starter on the viability and proteolytic activity of an adjunct culture of Lactobacillus plantarum I91 was assessed in two miniature cheese models, representative of Cremoso Argentino and Cheddar cheeses. Methods and Results: Cheeses with and without adjunct culture were made under controlled microbiological conditions and sampled during ripening for physicochemical and microbiological analyses. The addition of lactobacilli neither contributed to acid production nor caused changes to the composition of the cheeses. The strain studied exhibited good development and survival, and showed a similar growth pattern in both cheese matrices. The adjunct culture caused changes to secondary proteolysis of both cheese types, which were evidenced by modification of peptide profiles and the increase in the levels of some individual amino acids, as well as the total content of free amino acids. The changes observed were consistent with the acceleration of proteolysis in the two cheese models assayed. Conclusion: Lact. plantarum I91 has desirable and robust technological properties which makes it a suitable adjunct culture for cheese-making. Significance and Impact of Study: Other cultures and environmental conditions prevailing in the food may affect adjunct cultures viability and biochemical activities; this is the first report describing the successful performance of an adjunct culture of Lact. plantarum I91 in two different model cheese systems.